Maslahah Mursalah Approach on the Case of Ghoib Divorce in Islamic Law Perspective - Feoh, Jelita Marliana; Ben-Asher Siagian, Joy Daniel; Maladi Herwanto, Victoria Indry; Falyafil, Zakaria (Yustisia Tirtayasa : Jurnal Tugas Akhir, 2024)
This article aims to analyze the legal considerations of Judge in deciding the case of ghâib divorce and to trace the consideration of the decision which is the reason why the judge granted the case from a maslahah perspective. This research is normative legal research with a case study approach. The main source of this research is by using Law No. 1 of 1974, Government Regulation No. 9 of 1975, Compilation of Islamic Law, journals, articles, and fiqh books / books on maslahah, and related research issues. The result of this research is that the judge granted a divorce case before two years, to provide certainty of legal status in the Plaintiff's marriage with the Defendant, which was difficult to build. The judge's consideration in this case did not only refer to Article 19 letter (b) of Government Regulation No. 19 of 1975 jo. Article 116 letter (b), but also guided by Article 19 letter (f) of Government Regulation No. 19 of 1975 jo. Article 116 letter (f) with the process of summoning the ghâib. In this case, the ghâib cannot stand alone so that the panel of judges has another opinion by looking at the reason for the defendant's ghâib. When looking from the side of benefit in the five criteria of Dawâbit al- Maslahah, the judge's legal consideration in granting the plaintiff's claim with valid reasons according to the Law can uphold justice as an effort to maintain the preservation of religion and soul